PENGARUH BEAUTY INFLUENCER DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK FACIAL WASH GARNIER DI SURABAYA - Elisa Devi Pakan; Sugeng Purwanto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
There are many beauty products circulating in the market, therefore good marketing management is needed so that it can improve optimal purchasing decisions to achieve company goals. To achieve maximum purchase decisions, it is necessary to pay attention to the importance of beauty influencers and product quality. The purpose of the study was to determine the influence of beauty influencers and product quality on purchasing decisions for Garnier facial wash products in Surabaya. The population used is consumers who use Garnier facial wash. Determination of the sample through purposive sampling technique, to obtain 77 respondents. Data was collected through the distribution of questionnaires through google forms, then processed using the Partial Least Square (PLS) analysis technique. The results showed that beauty influencers and product quality had a significant positive effect on purchasing decisions.